2016
DOI: 10.1109/jbhi.2016.2608720
|View full text |Cite
|
Sign up to set email alerts
|

Toward Pervasive Gait Analysis With Wearable Sensors: A Systematic Review

Abstract: After decades of evolution, measuring instruments for quantitative gait analysis have become an important clinical tool for assessing pathologies manifested by gait abnormalities. However, such instruments tend to be expensive and require expert operation and maintenance besides their high cost, thus limiting them to only a small number of specialized centers. Consequently, gait analysis in most clinics today still relies on observation-based assessment. Recent advances in wearable sensors, especially inertial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
252
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(258 citation statements)
references
References 126 publications
1
252
0
5
Order By: Relevance
“…Recent reviews have examined wearable type, placement/location, algorithms and gait outcomes across a range of cohorts [23, [34][35][36]. In general author's remark on the heterogeneity of wearables, algorithms and gait outcomes due to a general lack of standardisation which make it difficult to compare and contrast across studies.…”
Section: Research Grade Wearablesmentioning
confidence: 99%
“…Recent reviews have examined wearable type, placement/location, algorithms and gait outcomes across a range of cohorts [23, [34][35][36]. In general author's remark on the heterogeneity of wearables, algorithms and gait outcomes due to a general lack of standardisation which make it difficult to compare and contrast across studies.…”
Section: Research Grade Wearablesmentioning
confidence: 99%
“…According to a recently published review article in the field of gait assessment using inertial sensors [25], only 30% of the 669 analyzed papers include relevant patient cohorts, and only 13% of the papers actually report on an application in an operational clinical environment required for the highest technology readiness levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most applications that are based on smart shoe technologies aim for impairment-specific gait signature assessment. A recent review article [25] gives an excellent overview regarding the applications of smart shoes in the medical domain, including fantastic overview tables that compare related work with specific items. In their study, the authors found that 29% of the included articles address Parkinson's disease, 17% Cerebral Palsy, and 13% orthoses, as summarized in Figure 6.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…The selected sample rate is currently used for several gait analysis systems [21]. The analog inputs of Arduino are internally connected to 10-bit analog-to-digital converters.…”
Section: System Descriptionmentioning
confidence: 99%